Enhanced magnetoresistance and electroresistance at high temperature in a nano-matrix manganite. (1st October 2022) - Xu, Hang; Huang, Ke; Li, Changjian; Qi, Ji; Li, Jiaming; Sun, Guiru; Wang, Fujun; Li, Haibo; Sun, Yong; Ye, Chen; Yang, Liu; Pan, Yongjing; et al.
Abstract: Magnetoresistance (MR) is highly exploitable to future spintronics devices, such as random-access memory, magnetic sensors, and spin-based neuromorphic electronics. Conventionally the enhanced MR in manganite always companies a sacrifice of Curie temperature, which limits its widespread application potential. Here we report a high-temperature survived MR in a La0.67 Sr0.33 MnO3 (LSMO) film grown on a piezoelectric substrate. The lattice mismatch between the film and substrate creates a self-assembled nano-matrix with two types of nanoscale matrices, namely [001]- and [101]-orientated LSMO magnetic domains. In this structure, the MR can reach -67% at even 350 K. Furthermore, the resistance of LSMO is electric-field-tunable to multiple resistance states by electrically modulating the biaxial strain imposed by the underlying piezoelectric substrate, an additional ∼14.2% electroresistance (ER) can be obtained. The achievements of high-temperature substantial MR and its electrical tunability in the nano-matrix manganite are of use to future multi-state memory devices in both spintronics and straintronics. Graphical abstract: Image, graphical abstract